Closeau : um modelo para classificação e controle de agentes pessoais computacionais - Leiradella, André Vargas Matos da Cunha e (2008)
Personal computer agents have increasingly played an important role assisting people to accomplish ordinary tasks, such as text editing and e-mail handling. In spite of their potential benefit, they can also be inconvenient and even prejudicial to their users. In this work a model to classify agents according to the axes intelligence and autonomy, and capable of diagnosing proactive dummies before they damage our lives is proposed. The model was implemented in the anti-spam domain, in which anti-spam agents help their users to automatically delete spam messages.